Evaluasi Dampak Manajemen Pendidikan Terhadap Bullying Pada Peserta Didik - Damayanti, Devi (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
The aim of this research is to evaluate the impact of educational management strategies and policies on the level of incidence and intensity and measure student, teacher and parent perceptions of the effectiveness of elementary school management in dealing with bullying; The research method used is descriptive qualitative; The data collection techniques used were observation, interviews and documentation; Data analysis used with Miles and Humbermen's theory is how to collect data, reduce data, present data, and draw conclusions; Data validity checking techniques using source and technique triangulation; The subjects in this research were the principal, head of curriculum, class teachers, and students; According to the results of this research, 1) Evaluation of the impact of the strategies that emerged included: religious learning strategies, teacher strategies through social care character education, collaboration strategies between teachers and parents in the form of parenting and school principal policies in dealing with bullying, so that students become more accustomed to and discipline in behavior at school and minimizing bullying behavior. 2) Measuring teachers' perceptions, namely acting decisively, anti-bullying campaigns, anti-bullying mentoring, classical and individual guidance, friendly attitudes, and providing instructions and understanding to students. Then the perception of parents is that disgraceful actions are carried out continuously, so that parents have the right to communicate well with teachers and actively involve themselves with their children, so that many perceptions are discussed in the solution to cases of bullying behavior